Design and construction of a fast synthetic modified vaccinia virus Ankara reverse genetics system for advancing vaccine development - Gao, Zhiqiang; Wang, Busen; Liu, Tianyu; Zhao, Zhenghao; Xu, Jinghan; Zhao, Xiaofan; Zhang, Zhe; Jia, Zuyuan; Yang, Yilong; Wu, Shipo; Chen, Wei; Hou, Lihua (Frontiers in Microbiology, 2025)
The modified vaccinia virus Ankara (MVA) is approved for use as a smallpox and monkeypox virus vaccine and was also designed as a popular recombinant viral vector for vaccine development and gene therapy. However, the extensive genomes of poxviruses present a significant challenge for the development of recombinant viral vaccines; therefore, it is essential to establish a user-friendly in vitro reverse genetic system. We systematically assembled the 180-kb MVA genome into a five-plasmid system, facilitating one-step packaging of the MVA virus. The MVA rescued using this system exhibited similar virological characteristics, including host cell tropism, growth kinetics, plaque size, and viral particles, comparable to those of wild-type MVA. Immunization with rescued MVA intramuscularly or subcutaneously triggered robust-specific immune responses and conferred protection against lethal attacks by the ectromelia virus in mice. We also developed a recombinant MVA-Luc-eGFP virus, which served as a tool for screening antiviral compounds against poxviruses. The synthetic MVA system efficiently generates recombinant vaccines with robust immune responses. These findings provide a novel and fast method for engineering large viral genomes with more specialized structures and lay a foundation for the advancement of more rapid and effective viral vector vaccines.